2021
DOI: 10.52586/4938
|View full text |Cite
|
Sign up to set email alerts
|

Key toolkits of non-pharmacological management in COPD: during and beyond COVID-19

Abstract: Introduction 3. Smoking cessation 4. Pulmonary rehabilitation (PR) 5. Telehealth applications 6. Clinical implications and recommendations 7. Conclusions 8. Author contributions 9. Ethics approval and consent to participate 10. Acknowledgment 11. Funding 12. Conflict of interest 13. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…This supports an earlier study by Hurst et al (2021), which showed that a significant number of people living with chronic lung disease believed that anti-infection measures should be applied to the wider community as well as to themselves beyond the COIVD-19 pandemic, particularly during the flu season [18]. For the future implementation of such measures among smokers and people living with chronic lung disease, special consideration should be paid to the benefits and potential harms of these measures, including cost and psychological harm [18,30].…”
Section: Discussionmentioning
confidence: 99%
“…This supports an earlier study by Hurst et al (2021), which showed that a significant number of people living with chronic lung disease believed that anti-infection measures should be applied to the wider community as well as to themselves beyond the COIVD-19 pandemic, particularly during the flu season [18]. For the future implementation of such measures among smokers and people living with chronic lung disease, special consideration should be paid to the benefits and potential harms of these measures, including cost and psychological harm [18,30].…”
Section: Discussionmentioning
confidence: 99%
“…The biological explanation could be the upregulation of the angiotensin-converting enzyme 2 receptors and the epithelial damage present in COPD patients and smokers. Another explanation is more mechanistic and involves hand-to-face movement, which would accelerate viral transmission [ 93 ], making the care of COPD patients with COVID-19 particularly challenging.…”
Section: Smoking Cessation During the Coronavirus Disease 2019 Pandem...mentioning
confidence: 99%
“…Pharmacological treatments such as bronchodilators, expectorants, antibiotics, and inhaled corticosteroids assist in controlling symptoms [3]. In parallel with non-pharmacological treatments, such as smoking cessation, pulmonary rehabilitation (PR), and vaccination, which play a role in self-management as well as maintaining and controlling the condition [4]. Technology can play an important role in facilitating the delivery of these treatments, promoting self-management.…”
Section: Introductionmentioning
confidence: 99%